MODEL MANAJEMEN PERSEDIAAN BAHAN BAKU PADA UKM BERBASIS WEB (DALAM KONSEP SUPPLY CHAIN MANAJEMENT) - Ishak Kholil (Paradigma, 2010)
Supply Chain (supply chain) concepts that can be adopted to provide products that are cheap, fast and quality. In the SME industry concept known as Supply Chain Management (SCM), the author tries to implement the concept of supply chain Management in raw materials inventory management model, the author tries to make the proposal a web-based approach. The prototype is web-based supply chain (web-based). By leveraging web technology, collaboration between organizations in a chain pasoki possible to implement. Kata Kunci: Supply Chain Management , UKM,   Web Base